Digital Marketing Management: Optimizing Social Media and Online Advertising for Business - Nany Librianty; Aryadi Aryadi; Rizqon Jamil Farhas; Fahmi Iqbal Firmananda; Rozaini Rozaini (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital marketing management is becoming an essential component of modern business strategies, especially for small businesses looking to expand their reach and increase customer engagement. Social media and online advertising offer businesses a great opportunity to strengthen their digital presence, but there are still many challenges to optimizing the effectiveness of their digital marketing strategies. This study aims to analyze the effectiveness of digital marketing strategies through social media and online advertising and to identify factors that contribute to increased customer transformation. The study examines how the integration of organic and paid marketing can guide a more efficient and sustainable strategy. The research method used is a quantitative approach with a descriptive and descriptive design. Data were collected by surveying 50 small businesses using social media and online advertising as part of their marketing strategy. Statistical analysis and regression techniques were used to identify the relationship between social media engagement, online advertising effectiveness, and customer transformation. The findings suggest that commitment to social media and online advertising-ROI has a significant impact on increasing customer transformation. Companies that take charge of their content-based digital marketing strategy and use data analysis in online advertising management will achieve optimal results than those that rely on one method.